PENGARUH INVESTASI PT.MCDERMOTT INDONESIA TERHADAP PERTUMBUHAN EKONOMI KOTA BATAM PASCA PEMBERLAKUAN SPECIAL ECONOMIC ZONE 2010-2011 - Hutahean Br Hutahean; Syafri Harto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study is an elaborate study of the influence of Investment PT McDermott Indonesia for Batam Economic Growth after Special Economic Zone held at 2010-2013. The purpose of this study was to clarify the effect of foreign investment on economic growth in Batam. Based on the concept of Foreign Direct Investment and the Theory of Investment.According to Krugman is the Capital of Foreign Direct investment is the flow of international capital from a country where companies establish or expand his company in another country. Batam, Bintan and Karimun are as Special Economic Zone in 2006, SEZ is a cooperation in placing one zone or more what ever investment and trade activity are done without intervention by local government, in other word local government only facilitator for investor through decreasing tax.Results of this study found that investment by PT McDermott Indonesia to give effect to the some sectors of economic growth in Batam, among others, development of value investment in the facility oil and gas sector, increase local employment decrease local poorness. From these results, it can mean that direct foreign investment provides benefits to the economy growth to the communities in Batam both locally and to the Government of Indonesia.Keywords : Foreign Direct Investment, Economic Growth, Special Economic Zone